Evaluating the Wear of Polycrystalline Diamond Compact Drill Bit Cutters using Indentation and Scratch Tests - Abbas, Rafid K.; Hassanpour, Ali R. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2018)
Abstract–Polycrystalline diamond compact (PDC) drill bits are widely used in oil and gas drilling. The wear of PDC cutters is a major problem during drilling. It leads to severe time losses which affect the overall drilling operation cost. Therefore, it is essential to evaluate the wear tendency for these cutters using predictive approaches. The present research is focused on studying the wear mechanisms of PDC cutters and the effect of their mechanical properties on the extent of wear. The volume of wear for the PDC cutters was determined experimentally using micro- and nano-scratch tests by implementing an approach based on the geometry of the removed material after micro- and nano-scratch tests. The experimental wear results were compared to the predictions from current models in the literature.Various wear models are evaluated for micro- and nano-scratch tests on both layers of the PDC samples. The study shows that the wear of the PDC cutters can be predicted from the material mechanical properties, applied load, sliding distance, and hardness of the PDC cutters. The study could be extended for the evaluation of wear intensity of PDC cutters from various manufactures without using the previous techniques of abrasion testing.